Socratic Self-Knowledge in Plato’s Politics and Democratic Deliberation - Arcand, Jeffrey (My University, 2024)
Socratic self-knowledge is rarely examined through the lens of politics. In this dissertation, I will make three main arguments relating to the social and political application of Socratic self-knowledge and its possible practical benefit for modern liberal democracy. These arguments will address the role of Socratic self-knowledge in Plato’s political philosophy, how Plato applies Socratic self-knowledge in his political work, and how it could benefit an inclusive deliberative democracy, rather than lead to Plato’s ideal epistemic aristocracy. In the first chapter, I argue that Socratic self-knowledge is a cornerstone of Plato’s political philosophy. This includes comparing similar concepts, although not always using the explicit language of “self-knowledge,” throughout the Platonic corpus. In the second and third chapters, I examine the types of persuasion that Plato critiques and seems to endorse and how virtuous or artful rhetoric is applied in the Republic and Laws. I argue that Plato applies the concept of artful rhetoric established in the Phaedrus to the imagined societies of the Republic and Laws, in part, to produce the same political results that a society with genuine widespread Socratic self-knowledge would produce, without cultivating genuine self-knowledge in the citizenry. The fourth chapter argues against Plato’s position that that a society with widespread self-knowledge would result in a technocratic aristocracy as he seems to assume in the Charmides, Republic, and, to a lesser extent, the Laws. Instead, I argue that a cultural value of epistemic self-awareness would be a great benefit to collaborative deliberation. By accepting that we ourselves do not know all there is to know about any possible political decision, and that others may have important relevant knowledge, we will become more likely to engage as collaborators rather than as adversaries and to consider other perspectives and positions more seriously.
Keywords: Ancient Philosophy; Plato; Political Philosophy; Democracy; Self-knowledge; Socrates